A REVIEW OF CASES OF DEVELOPMENT OF ACUTE HEPATIC INSUFFICIENCY DUE TO THE INTAKE OF BIOLOGICALLY ACTIVE ADDITIVES - M. L. Maksimov; S. A. Simakova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Around the world, the use of dietary supplements is common and can be purchased without consulting a doctor. It is believed that more than 50 % of adults worldwide use dietary supplements. The article deals with the regulation of the market of biologically active additives worldwide, including the Russian Federation, the safety of use, the development of undesirable reactions. Information was searched on databases on the development of medicinal liver damage associated with the use of biologically active additives containing green tea extract, usninic acid, 1,3-dimethylamylamine, vitamin A, anabolic androgenic steroids, linoleic acid, ephedra, Garcinia Cambogia used for weight loss. The use of anabolic steroids has revealed an increased risk of adverse reactions from the liver, cardiovascular and endocrine systems. The use of dietary supplements containing green tea extract can lead to severe liver damage. Analysis of adverse reactions after the use of dietary supplements under the trade name Herbalife revealed cases of falsification of drugs. The use of drugs containing vitamin a in high doses, ephedra, Garcinia Cambogia led to increased hepatic transaminases, mental disorders, osteoporosis, anorexia.